The Marketability of Technical Graduates from Higher Educational Institutions (HEIs) Offering Technical and Vocational Education and Training (TVET): A Case from Malaysia - Rajadurai J.; Sapuan N.M.; Daud S.; Abidin N. (Springer Singapore, 2023)
Technical, Vocational Education and Training has been viewed as a means of developing a nation. The marketability of technical graduates is reliant on whether these graduates possess the attributes demanded by their respective industries. Hence, this study aims to investigate the gap between the key attributes of Higher Education Institutions (HEIs) technical graduates and their actual performance of these attributes in employment as assessed by the Human Resource Managers. The dimensions of these attributes are investigated in four main areas, namely knowledge, skills, abilities and personality. Structured questionnaires were distributed to the Human Resource Managers of listed companies in Malaysia that employed technical graduates. The importance performance analysis, a form of quadrant analysis, was employed to analyse the data. The results show that all items pertaining to the personality dimension were placed in the quadrant keep up the good work (high importance/high performance). The knowledge dimension consisting of tacit and explicit knowledge types was placed in the concentrate here quadrant (high importance/low performance). Skills (soft skills and hard skills) and intellectual abilities were placed in the low priority quadrant. Physical ability was the only item placed in the possible overkill quadrant. HEIs should take immediate action to review the attributes located in the concentrate here and the possible overkill quadrants. This approach will enable HEIs to take corrective action and instigate efforts to improve the attributes considered to be important in producing marketable technical graduates to support the human capital required by the nation to be a developed nation by the year 2020. 2018, De La Salle University.